Conductive diamond electrode, manufacturing method thereof, and electrolysis unit
The conductive diamond electrode with a diamond powder layer and inorganic matrix addresses scalability and durability issues in existing diamond electrodes, achieving high performance under harsh electrolytic conditions for industrial applications.
Patent Information
- Application Number
- JP2020201358
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-03
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2040-12-03
AI Technical Summary
Existing diamond electrodes face challenges in scalability for industrial use due to difficulties in manufacturing large-area thin-film diamond electrodes, and coating-type diamond electrodes lack durability under harsh electrolytic conditions such as high potential and concentrated sulfuric acid.
A conductive diamond electrode with a conductive diamond powder layer containing conductive diamond powder and a matrix primarily composed of inorganic materials, such as silica, which provides high durability and excellent electrolytic performance.
The proposed electrode achieves high durability and excellent electrolytic performance even under harsh conditions, enabling efficient sulfuric acid electrolysis and potential use in recycling composite materials and semiconductor manufacturing.
Smart Images

Figure 0007665138000001 
Figure 0007665138000002 
Figure 0007665138000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive diamond electrode, a manufacturing method thereof, and an electrolysis unit equipped with the conductive diamond electrode. [Background technology]
[0002] Carbon fiber composite materials, such as lightweight and strong carbon fiber reinforced plastics (CFRP), are advanced materials that contribute greatly to reducing the weight of automobiles, and are also important materials from the perspective of improving fuel efficiency through weight reduction and complying with environmental regulations. However, because carbon fiber is very stable both chemically and physically, it remains for many years after disposal, and there was an issue that it contributes to marine plastic pollution. In recent years, the electrolytic sulfuric acid process, which can easily decompose organic matter, has been attracting attention as a recycling process for carbon fiber composite materials. Since the electrolytic sulfuric acid process requires harsh electrolysis conditions, such as high potential and concentrated sulfuric acid, the electrodes used in sulfuric acid electrolysis must be highly durable.
[0003] Conductive boron-doped diamond (BDD), which is diamond doped with boron, has excellent physical and chemical stability and can efficiently decompose sulfuric acid at high potential without decomposing itself, making it a promising electrode material for sulfuric acid electrolysis. For example, Patent Document 1 discloses a technique for recovering reinforcing materials (carbon fibers) from CFRP by an electrolytic sulfuric acid method using a thin-film diamond electrode (so-called diamond electrode) in which BDD is coated on the surface of a metal plate in a thin film form. Thin-film diamond electrodes are usually manufactured by directly coating BDD on a substrate by chemical vapor deposition (CVD). Furthermore, as an electrode with enhanced adhesion between the BDD and the electrode substrate, Patent Document 2 discloses a coated diamond electrode obtained by applying a paint in which BDD powder (BDDP) is dispersed in a resin binder (ion exchange resin, or insulating binder and silicone rubber) to an electrode substrate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-171830 A [Patent Document 2] Patent No. 6506924 Summary of the Invention [Problem to be solved by the invention]
[0005] However, with the thin-film diamond electrode described in Patent Document 1, it is difficult to increase the size of the CVD equipment used to coat the substrate with BDD, making it difficult to manufacture large-area diamond electrodes, and improvements are needed in terms of scale-up for industrial use. In this regard, the coated diamond electrode described in Patent Document 2, which is manufactured by applying a resin binder in which BDDP is dispersed to a substrate, can accommodate larger electrode areas, but its durability is insufficient for use under the harsh electrolytic conditions of high potential and concentrated sulfuric acid in the electrolytic sulfuric acid method.
[0006] Therefore, the present invention has been made in consideration of the above problems, and an object of the present invention is to provide an electrode that has high durability even under harsh electrolytic conditions of strong acid and high voltage, has excellent electrolytic performance, and can be made large in area. [Means for solving the problem]
[0007] As a result of intensive research into solving the above problems, the inventors discovered that the above object could be achieved by providing an electrode having a conductive diamond powder layer containing conductive diamond powder and a matrix mainly containing inorganic material, and thus completed the present invention.
[0008] That is, the present invention is as follows. [1] A method for producing a conductive diamond electrode, comprising: The conductive diamond electrode is An electrode having a substrate and a layer of conductive diamond powder on a surface of the substrate, The conductive diamond powder layer includes at least a conductive diamond powder and a matrix mainly including an inorganic material, The inorganic material mainly contains silica. fruit, However, a conductive diamond electrode except that the conductive diamond powder layer is bonded to at least one surface of the substrate by a conductive brazing material; The method for producing the conductive diamond electrode includes the steps of: a slurry preparation step of preparing a slurry in which a powder containing a conductive diamond powder and a matrix forming material that forms a matrix of the conductive diamond powder layer are dispersed; a coating step of coating a substrate with the slurry prepared in the slurry preparation step to form a coating layer; a film-forming step of forming a film by subjecting the coating layer formed in the coating step to a heat treatment; having The matrix forming material is tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltriisopropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltriisopropoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltriisopropoxysilane, butyltrimethoxysilane, butyltriethoxysilane, butyltriisopropoxysilane, hexyltrimeth silane, hexyltriethoxysilane, hexyltriisopropoxysilane, octyltrimethoxysilane, octyltriethoxysilane, octyltriisopropoxysilane, decyltrimethoxysilane, decyltriethoxysilane, decyltriisopropoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane, octadecyltriisopropoxysilane, vinylchlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl (meth)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, p-aminophenyltrimethoxysilane, p-styryltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, Acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatopropyltriethoxysilane, 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane, A conductive diamond electrode characterized by Manufacturing method . [2] The conductive diamond electrode according to [1], wherein the surface of the conductive diamond powder has an oxygen atom concentration of 1% or more as calculated using X-ray photoelectron spectroscopy (XPS). Manufacturing method . [3] The conductive diamond electrode according to [1] or [2], wherein the content of the inorganic material in the matrix is 90 mass % or more. Manufacturing method . [4] The electrode according to any one of [1] to [3], wherein a mass ratio of the conductive diamond powder to the silica (conductive diamond powder:silica) is 2:8 to 8:2. Manufacturing method . [5] The conductive diamond electrode according to any one of [1] to [4], wherein the conductive diamond powder has an average particle size of 5 nm to 100 μm. Manufacturing method . [6] The conductive diamond electrode according to any one of [1] to [5], wherein the conductive diamond powder layer has an average thickness of 5 nm to 500 μm. Manufacturing method. [7 ] The mass ratio of the conductive diamond powder to the matrix-forming material (conductive diamond powder / matrix-forming material) is 25 to 400 mass%. [1] - [6]The method for producing the conductive diamond electrode according to the present invention 。 [8 ] In the coating step, coating is performed by a spin coating method. 1 ]~[ 7 ] A method for producing a conductive diamond electrode according to any one of the following methods. 。 [9 ] [1]~[ 8 13. The conductive diamond electrode according to any one of claims 1 to 12. A conductive diamond electrode is manufactured by the manufacturing method of the present invention, and the obtained conductive diamond electrode is used The electrolysis unit is characterized by Manufacturing method . [ 10 ] [9]. An electrolysis unit is produced by the method for producing an electrolysis unit according to the present invention, Characterized by its use in the electrolysis of sulfuric acid , electric Use of solution units. [ 11 ] [ 9
[0023] The electrolysis unit according to Manufacturing method Using an electrolysis unit manufacturing step of manufacturing an electrolysis unit; Using the electrolysis unit obtained in the electrolysis unit manufacturing step A solution preparation step of electrolyzing sulfuric acid to obtain a solution containing an oxidizing active species; a removing step of removing an organic material pattern and / or impurities from a semiconductor substrate using the solution containing the oxidizing active species obtained in the solution preparing step; A method for manufacturing a semiconductor, comprising the steps of: [ 12 ] [ 9
[0023] The electrolysis unit according to Manufacturing method Using an electrolysis unit manufacturing step of manufacturing an electrolysis unit; Using the electrolysis unit obtained in the electrolysis unit manufacturing step A solution preparation step of electrolyzing sulfuric acid to obtain a solution containing an oxidizing active species; a reinforcing material recovery step of decomposing the resin of a composite material composed of a resin and a reinforcing material using the solution containing the oxidizing active species obtained in the solution preparation step, and extracting the reinforcing material; A method for treating a composite material, comprising: [ 13 ] [ 122. A method for producing a composite material, comprising using a reinforcing material extracted by the method for treating a composite material described in claim 1. Effect of the Invention
[0009] According to the present invention, it is possible to provide an electrode that has high durability even under harsh electrolytic conditions of strong acid and high voltage, has excellent electrolytic performance, and can be made large in area. [Brief description of the drawings]
[0010] [Figure 1] 1 is a diagram showing a scanning electron microscope (SEM) image of the surface of one embodiment (Example 1) of the conductive diamond electrode according to the present invention. The upper figure is a low-magnification image (magnification 1,000 times), and the lower figure is a high-magnification image (magnification 20,000 times) enlarged around the dotted line part in the upper figure. [Diagram 2] FIG. 2 is a diagram showing cyclic voltammetry (CV) of the embodiments (Examples 1 to 3) of the conductive diamond electrode according to the present invention and other electrodes (Comparative Examples 1 and 2). [Diagram 3] FIG. 2 is a diagram showing potential changes during sulfuric acid electrolysis by constant current electrolysis for the embodiments (Examples 1 and 3) of the conductive diamond electrode according to the present invention and another electrode (Comparative Example 2). [Figure 4] FIG. 2 is a diagram showing the potential change during electrolysis in concentrated sulfuric acid by constant current electrolysis for one embodiment (Example 1) of the conductive diamond electrode according to the present invention. [Diagram 5] FIG. 2 is a graph showing the concentration and generation efficiency of oxidizing active species generated during electrolysis of concentrated sulfuric acid by constant current electrolysis for one embodiment (Example 1) of the conductive diamond electrode according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the following description, and can be modified in various ways within the scope of the gist of the present invention.
[0012] [electrode] The conductive diamond electrode of this embodiment is an electrode having a substrate and a conductive diamond powder layer on the surface of the substrate, and the conductive diamond powder layer contains at least conductive diamond powder and a matrix mainly containing an inorganic material.
[0013] [Base material] The substrate constituting the conductive diamond electrode of this embodiment is not particularly limited, but for example, titanium, chromium, nickel, zirconium, niobium, molybdenum, tantalum, tungsten, etc. pure metal, titanium alloy, stainless steel, brass, duralumin, etc. alloy metal, gold, silver, platinum, palladium, rhodium, iridium, ruthenium, osmium, etc. precious metal are preferably used. Among them, titanium and stainless steel are preferable from the viewpoint of excellent corrosion resistance, relatively cheap and easy to obtain. The shape and size of the substrate are not particularly limited and may be appropriately determined depending on the application of the electrode of this embodiment.
[0014] [Conductive diamond powder layer] The conductive diamond electrode of this embodiment has a conductive diamond powder layer on the surface of a substrate. The conductive diamond powder layer may be provided on at least a part of the surface of the substrate.
[0015] The conductive diamond powder layer contains at least conductive diamond powder and a matrix mainly containing an inorganic material. Since the matrix mainly contains an inorganic material, the conductive diamond powder layer has excellent adhesion to the substrate and high durability capable of withstanding harsh electrolytic conditions of strong acid and high voltage.
[0016] The average thickness of the conductive diamond powder layer can be appropriately selected depending on the particle size and content of the conductive diamond powder, but is preferably 5 nm to 500 μm, more preferably 7 nm to 200 μm, and even more preferably 10 nm to 150 μm. If the average thickness is 5 nm or more, excellent electrolytic performance can be exhibited even under harsh electrolytic conditions of strong acid and high voltage, and if it is 500 μm or less, the electrical resistance is sufficiently low and energy loss can be reduced. In the present disclosure, the average thickness of the conductive diamond powder layer is a value measured using a scanning electron microscope (SEM).
[0017] [[Conductive diamond powder]] The conductive diamond powder contained in the conductive diamond powder layer is dispersed in a matrix. Examples of conductive diamond powder include boron-doped diamond powder (BDDP), phosphorus-doped diamond powder, nitrogen-doped diamond powder, etc. Among these, BDDP is preferred from the viewpoint of obtaining diamond powder with low resistance.
[0018] The conductive diamond powder has a particulate base material and a conductive diamond film on at least a portion of the surface of the particulate base material, and the conductive diamond film may be coated on only a portion of the surface of the particulate base material, or the entire surface of the particulate base material may be coated with the conductive diamond film. Here, the term "conductive" in the conductive diamond powder means that the powder conductivity is 0.01 S / cm or more. The material used for the particulate substrate is not particularly limited as long as it is not melted or deformed by the heat applied during the formation of the conductive diamond film, and can be appropriately selected according to the purpose, and examples thereof include natural or synthetic diamond particles such as insulating diamond particles commercially available as abrasive grains, metal particles such as silicon and molybdenum, metal alloy particles such as boron nitride, and metal oxide particles such as quartz and alumina. Among these, natural diamond particles and synthetic diamond particles are preferred. These particulate base materials may be used alone or in combination of two or more.
[0019] Artificial diamond powder can be produced by CVD methods such as thermal CVD, RF plasma CVD, and hot filament CVD, PVD methods such as ion beam methods and ionized deposition methods, and high temperature and high pressure methods.
[0020] Methods for forming a conductive diamond layer on the surface of a base particle include, for example, methods for growing a diamond layer containing a doping element on the base material by CVD methods such as plasma CVD, thermal CVD, photo CVD, and laser CVD. The carbon and doping element that are the materials of the conductive diamond layer preferably have a ratio of the number of atoms of the doping element to the number of atoms of carbon (doping element / carbon) of 10 to 100,000 ppm, more preferably 100 to 50,000 ppm, and even more preferably 1000 to 30,000 ppm. When the ratio of the number of atoms of the doping element is within the above range, conductive diamond particles that have high crystallinity and excellent conductivity can be obtained.
[0021] Examples of carbon sources for the carbon that constitutes the conductive diamond layer include aliphatic hydrocarbons such as methane, ethane, propane, butane, pentane, hexane, heptane, and octane; alicyclic hydrocarbons such as cyclohexane; aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene; alcohols such as methanol, ethanol, isopropyl alcohol, and butanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ethers such as diethyl ether, dimethoxyethane, tetrahydrofuran, and dioxane; and esters such as methyl acetate, ethyl acetate, isopropyl acetate, and butyl acetate. These carbon sources may be used alone or in combination of two or more.
[0022] When the doping element is boron, boron sources include, for example, boron oxide, boron carbide, boron nitride, boric acid, diborane, triethylborane, trimethoxyborane, triethoxyborane, tripropoxyborane, tri(1,1-dimethylethoxy)borane, and the like. These boron sources may be used alone or in combination of two or more.
[0023] The shape of the conductive diamond powder is not particularly limited, and examples thereof include spherical, polyhedral, needle, and spindle shapes. The conductive diamond powder may be a mixture of particles of different sizes. The conductive diamond powder preferably has an average particle size of 5 nm to 100 μm, more preferably 50 nm to 10 μm, and even more preferably 100 nm to 1 μm. When the average particle size is 5 nm or more, a conductive diamond powder with good crystallinity can be obtained, and when the average particle size is 100 μm or less, the conductive diamond powder can be well dispersed in the matrix. In the present disclosure, the average particle size of the conductive diamond powder is the volume average particle size measured by dynamic light scattering (DLS), and specifically, can be measured by the method described in the examples below.
[0024] The surface of the conductive diamond powder preferably has an oxygen atom concentration of 1% or more, more preferably 5% or more, and even more preferably 7% or more, as calculated using X-ray photoelectron spectroscopy (XPS). When the oxygen atom concentration is 1% or more, the adhesiveness between the conductive diamond powder and the substrate is high, and the conductive diamond powder layer tends to become an electrode that functions stably even under electrolytic conditions of strong acid and high voltage. Specifically, the measurement of the surface concentration of oxygen atoms by XPS can be carried out by the method described in the Examples below.
[0025] The content of the conductive diamond powder is preferably 90 mass% or more, more preferably 95 mass% or more, and even more preferably 98 mass% or more, with the total mass of the conductive powder contained in the conductive diamond powder layer being 100 mass%.
[0026] [[Other conductive powders]] In order to ensure, maintain or improve the conductivity, durability, etc. of the electrode, the conductive diamond powder layer of the electrode of this embodiment may contain, in addition to the conductive diamond powder, other conductive powders such as, for example, tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), zinc oxide (ZnO), indium oxide (In2O3), tin oxide (SnO2), IZO (In-Zn-O), IGZO (In-Ga-Zn-O), carbon nanotubes, fullerenes), carbon black, conductive assistants such as graphene, and metal particles such as Ag, Au, Cu, Pd, Pt, Al, etc. The other conductive powders may be used alone or in combination of two or more kinds. The content of the other conductive powders is preferably 10 mass % or less, with the total mass of the conductive powders contained in the conductive diamond powder layer being 100 mass %.
[0027] [[Matrix]] The matrix of the conductive diamond powder layer mainly comprises inorganic materials. The matrix "mainly" containing an inorganic material means that the content of the inorganic material in the matrix is 70% by mass or more, with the matrix being 100% by mass. The content of the inorganic material in the matrix is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 97% by mass or more.
[0028] From the viewpoints of strong acid resistance, securing mechanical strength, and good controllability of in-plane stress, it is preferable that the inorganic material mainly contains silica. Although there is no particular limitation, inorganic materials other than silica are preferably those that are strong acid resistant, such as metal oxides such as titania, zirconia, and alumina. Incidentally, the inorganic material "mainly" contains silica means that the content of silica in the inorganic material is more than 50 mass % with the inorganic material being 100 mass %.
[0029] The matrix of the conductive diamond powder layer may contain, in addition to inorganic materials, organic materials such as resins, and organic-inorganic composite materials in which inorganic oxides and organic molecules are combined. The content of such matrix constituent components other than the inorganic material is preferably 30% by mass or less, with the matrix being 100% by mass.
[0030] In the conductive diamond powder layer, the mass ratio of the conductive diamond powder to the inorganic material (conductive diamond powder:inorganic material) is preferably 1:9 to 9:1, more preferably 2:8 to 8:2, even more preferably 3:7 to 7:3, and even more preferably 4:6 to 6:4. When the mass ratio of the conductive diamond powder to the inorganic material is within the above range, the conductive diamond powder has excellent density and can exhibit excellent electrolytic performance. In particular, the mass ratio of the conductive diamond powder to silica (conductive diamond powder:silica) in the conductive diamond powder layer is preferably 2:8 to 8:2, more preferably 3:7 to 7:3, and further preferably 4:6 to 6:4.
[0031] [Method of manufacturing conductive diamond electrodes] The manufacturing method of the conductive diamond electrode of this embodiment includes a slurry preparation step of preparing a slurry in which a powder containing conductive diamond powder and a matrix forming material that forms the matrix of the above-mentioned conductive diamond powder layer are dispersed, a coating step of coating a substrate with the slurry prepared in the slurry preparation step to form a coating layer, and a film formation step of subjecting the coating layer formed in the coating step to heat treatment to form a film.
[0032] [[Slurry preparation process]] In the slurry preparation process, a powder containing conductive diamond powder, a matrix-forming material that forms the matrix of the conductive diamond powder layer, and a solvent are stirred and mixed to prepare a slurry in which the powder containing conductive diamond powder and the matrix-forming material are dispersed in the solvent.
[0033] The powder containing conductive diamond powder comprises conductive diamond powder and, optionally, other powders as described above. Conductive diamond powder may be used after surface treatment according to purpose. Surface treatment may include, for example, hydrogen termination, oxygen termination, halogenation, ferrocene modification, sulfo group modification, quaternary ammonia group termination, organic functional group modification (carboxyl group termination, etc.), and other chemical modification treatments, thermal treatments, etc. Among them, oxygen termination is preferably carried out from the viewpoint of improving compatibility with matrix forming material. In particular, when coating is performed by spin coating in the coating step described below, it is preferable to subject the conductive diamond powder to oxygen termination treatment (hydrophilization treatment) in order to improve affinity with the substrate and the slurry solvent.
[0034] The matrix-forming material includes raw materials of the inorganic material that is the main component of the matrix, and optionally raw materials of other matrix components. As a matrix forming material for forming a matrix containing silica as an inorganic material, a known material capable of forming a sol-gel film can be appropriately used, and examples of such a material include tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltriisopropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltriisopropoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltriisopropoxysilane, butyltrimethoxysilane, and the like. silane, butyltriethoxysilane, butyltriisopropoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, hexyltriisopropoxysilane, octyltrimethoxysilane, octyltriethoxysilane, octyltriisopropoxysilane, decyltrimethoxysilane, decyltriethoxysilane, decyltriisopropoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane, octadecyltriisopropoxysilane, vinylchlorosilane, vinyltrimethoxysilane, vinyltriisopropoxysilane isethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, p-aminophenyltrimethoxysilane, p-styryltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltrimeth xysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,It is preferable that the silane-containing compound contains at least one selected from the group consisting of 3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane.
[0035] As a matrix-forming material for forming a matrix containing titania, zirconia, or alumina as an inorganic material, any known material capable of forming a sol-gel film can be appropriately used. These may be used alone or in combination of two or more.
[0036] As the solvent, an organic solvent such as methanol or ethanol can be suitably used. Furthermore, an inorganic acid such as nitric acid, hydrochloric acid, or ammonia, or an aqueous alkali solution may be added as a reaction catalyst.
[0037] In preparing the slurry, the mass ratio of the conductive diamond powder to the matrix-forming material (conductive diamond powder / matrix-forming material) can be appropriately selected, but is preferably 10 to 900 mass%, more preferably 25 to 400 mass%, even more preferably 40 to 200 mass%, and even more preferably 60 to 150 mass%. When the mass ratio of the conductive diamond powder is within the above range, a conductive diamond powder layer having sufficient conductivity and stability can be obtained.
[0038] [[Coating process]] In the coating step, the slurry prepared in the slurry preparation step is applied to a substrate to form a coating layer. From the viewpoint of improving the affinity with the slurry, the substrate may be subjected to a hydrophilization treatment such as UV / ozone treatment before coating.
[0039] The coating method is not particularly limited, and examples thereof include spin coating, dip coating, laminar flow coating, printing, spray coating, bar coating, etc. In particular, when the substrate is plate-shaped, spin coating is preferred because it can be uniformly spread (coated) with a small amount of slurry.
[0040] When coating by spin coating, the rotation speed and rotation time of the substrate are appropriately selected depending on the viscosity of the slurry, the desired thickness of the conductive diamond layer, etc. For example, the rotation speed of the substrate can be 1000 to 30,000 rpm and the rotation time can be 10 to 300 seconds.
[0041] [[Film forming process]] In the film-forming step, the coating layer formed in the coating step is subjected to a heat treatment to form a film. Examples of the method for forming a film by heat treatment include the sol-gel method, hydrothermal reaction, etc. The sol-gel method is preferred because it can be carried out at room temperature.
[0042] The heat treatment temperature is preferably from 50 to 500°C, and more preferably from 100 to 250°C.
[0043] [Electrolysis unit] The electrolysis unit of this embodiment is equipped with the conductive diamond electrode of this embodiment described above. The configuration of the electrolysis unit other than the conductive diamond electrode of this embodiment (counter electrode, diaphragm, etc.) is not particularly limited, and conventionally known ones can be used depending on the electrolysis application.
[0044] The electrolysis unit of this embodiment includes the electrodes of this embodiment described above, and therefore can be used for severe electrolysis of strong acids and high voltages, such as the electrolysis of sulfuric acid. When sulfuric acid is electrolyzed using the electrolysis unit of this embodiment, a solution containing oxidizing active species (OH radicals, peroxomonosulfuric acid, peroxodisulfuric acid, ozone, hydrogen peroxide, etc.) can be obtained.
[0045] The electrolysis unit of the present embodiment can be used for electrolyzing sulfuric acid. Therefore, for example, the electrolysis unit of the present embodiment can be used in a semiconductor manufacturing method including a solution preparation step of electrolyzing sulfuric acid using the electrolysis unit of the present embodiment to obtain a solution containing an oxidizing active species, and a removal step of removing an organic material pattern and / or impurities from a semiconductor substrate by using the solution containing the oxidizing active species obtained in the solution preparation step. In the removal process, the semiconductor substrate is immersed in a solution containing an oxidizing active species, whereby the organic material pattern (e.g., photosensitive resin) and / or impurities (e.g., metals, particles) on the semiconductor substrate are decomposed and removed from the semiconductor substrate.
[0046] The electrolysis unit of this embodiment can be used in a method for treating a composite material, the method comprising: a solution preparation step of electrolyzing sulfuric acid using the electrolysis unit of this embodiment to obtain a solution containing oxidizing active species; and a reinforcing material recovery step of decomposing a resin of a composite material composed of a resin and a reinforcing material using the solution containing the oxidizing active species obtained in the solution preparation step, and extracting the reinforcing material. The reinforcing material extracted by the method for treating a composite material can be recycled by being reused in the production of a composite material. In the reinforcing material recovery process, a composite material consisting of a resin and a reinforcing material is immersed in a solution containing an oxidizing active species, whereby the resin is decomposed, and the decomposition products are dissolved in the solution. The reinforcing material can then be recovered by removing it from the solution.
[0047] The resin contained in the composite material is not particularly limited as long as it is generally used in composite materials, and examples thereof include thermosetting resins and thermoplastic resins. Examples of thermoplastic resins include super engineering plastics such as polyether ether ketone and polyether sulfone, and general-purpose plastics such as polyester, nylon, polypropylene, and polyethylene. Examples of thermosetting resins include epoxy resins, bismaleimide resins, polyimide resins, unsaturated polyester resins, and vinyl ester resins. These resins may be used alone or in combination of two or more.
[0048] Examples of reinforcing materials contained in composite materials include carbon fibers, glass fibers, metal fibers, organic high-strength fibers such as aramid, organic and inorganic nanofibers such as carbon nanotubes and cellulose nanofibers, etc. These fibers may be of one type alone or may be hybrid fibers made by combining two or more types. EXAMPLES
[0049] The present invention will be described below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples.
[0050] The measurement methods used in the examples and comparative examples are as follows.
[0051] (1) Average particle size of conductive diamond powder The average particle size (nm) of the BDDP used in the examples was determined using a dynamic light scattering (DLS) measuring device (NICOMP380, manufactured by Particle Sizing Systems).
[0052] (2) Oxygen atom concentration on the surface of conductive diamond powder For the BDDP used in the examples, the concentration (%) of oxygen atoms on the BDDP surface was determined by X-ray photoelectron spectroscopy (XPS). Specifically, the measurement was performed under the following conditions, and the concentration of oxygen atoms was calculated based on the peak area of the oxygen 1s spectrum (525 to 545 eV). The measurement was performed at three points on the BDDP, and the measurement results were averaged. <XPS measurement conditions> Equipment used: Kratos Analytical, AXIS-NOVA Excitation source: monoAlKα radiation (accelerating voltage 15 kV) Analysis size: 100μmφ Photoelectron extraction angle: 90° Scan range: 0~1100eV
[0053] (3) Cyclic voltammetry (CV) The electrodes obtained in the examples and comparative examples were measured for CV in 1M H2SO4 using an electrochemical measurement device (Hokuto Denko, HZ-7000). A silver / silver chloride (Ag / AgCl) electrode was used as the reference electrode, and a platinum wire was used as the counter electrode. The measurement results are shown in Figure 2. In sulfuric acid electrolysis, the generation of peroxodisulfuric acid, an oxidizing active species, begins with the generation of OH radicals produced by the electrolysis of water. The generation of OH radicals competes with the generation of oxygen (O2), so the greater the overpotential for oxygen generation, the more efficient the generation of OH radicals becomes, which is thought to be advantageous for the generation of peroxodisulfuric acid, i.e., sulfuric acid electrolysis.
[0054] (4) Constant current electrolysis of sulfuric acid (i) Constant current electrolysis of 1M H2SO4 A two-chamber electrolysis cell (EC Frontier, VB9) was used, and the electrodes obtained in Examples 1 and 3 and Comparative Example 2 (electrode area: 0.5 cm ) were used as counter electrodes using platinum wire. 2 ) was used to carry out constant current electrolysis of 1M H2SO4 (electrolysis current: 0.3 mA). The measurement results are shown in Figure 3. (ii) Constant current electrolysis of 10M H2SO4 A two-chamber electrolysis cell (EC Frontier, VB9) was used, and the electrodes obtained in Example 1 and Comparative Example 1 (electrode area: 0.5 cm ) were used as counter electrodes using platinum wire. 2) was used to carry out constant current electrolysis of 10M H2SO4. The electrolysis current value was set so that the electrolysis potential was about +2 to +3 V vs. Ag / AgCl, and electrolysis was carried out for 90 minutes. The measurement results of Example 1 (electrolysis current: 0.2 mA, 0.25 mA, 0.3 mA) are shown in FIG. (iii) Concentration and generation efficiency of oxidizing active species The concentration (mM) of the oxidizing active species contained in sulfuric acid after constant current electrolysis of 10M H2SO4 above (ii) was measured by reacting potassium iodide with the oxidizing active species to liberate iodine, and then titrating the total iodine concentration with a sodium thiosulfate standard solution (potassium iodide titration method). In addition, the generation efficiency of oxidizing active species per C of applied charge (μmol / C) was calculated. The measurement results of Example 1 are shown in Fig. 5. In Fig. 5, the concentration of oxidizing active species is shown by white squares, and the generation efficiency of oxidizing active species is shown by black circles. The concentrations and amounts of oxidizing active species were expressed as the amount of iodine (I2) equivalent in titration.
[0055] [Example 1] (Preparation of BDDP) Diamond powder (Element Six, Micron+MDA0-0.5, average particle size: approximately 300 nm) was used as a substrate, and an as-grown BDDP was fabricated by growing a BDD layer on the substrate surface using microwave plasma CVD. A mixture of acetone and methanol (9:1, v / v) was used as the carbon source, trimethoxyborane was used as the boron source, and the ratio of the number of boron atoms to the number of carbon atoms (boron / carbon) was set to 20,000 ppm. The CVD conditions are shown below. The as-grown BDDP was subjected to thermal oxidation treatment (oxygen termination treatment) at 425℃ for 5 hours in air using a muffle furnace to obtain BDDP. <CVD conditions> Microwave power: 1300W Pressure: 50 Torr Hydrogen gas flow rate: 400sccm Boron / Carbon Ratio: 20,000ppm Growth time: 8h The average particle size of the obtained BDDP was 350 nm, and the oxygen atom concentration on the BDDP surface was 7.6%. (Preparation of coated BDD electrodes) 0.34 g of the BDDP obtained above, 0.5 mL of tetraethoxysilane, 1.3 mL of ethanol, and 1.3 mL of 4.2 M nitric acid were mixed and stirred for 24 hours to prepare a slurry (BDDP:tetraethoxysilane mass ratio = 4:6). 0.1 mL of the slurry was dropped onto the surface of a titanium plate (1.5 cm x 1.5 cm) that had been washed and hydrophilized using a UV / ozone treatment device (Sen Special Light Source, PL17-110), and a liquid film was developed by spin coating (rotation speed: 3000 rpm, time: 120 seconds). After that, a baking treatment was performed at 120 °C for 1 hour to obtain a coated BDD electrode. The surface of the obtained BDD electrode was observed with a scanning electron microscope (SEM) (JEOL, JSM-7600F). The obtained SEM image is shown in Figure 1. The upper image is a low-magnification image (1,000x), and the lower image is a high-magnification image (20,000x) enlarged around the dotted line in the upper image. Although fine cracks were visible, no exposed substrate was observed, and the BDDP layer was well formed. Furthermore, the results of constant-current electrolysis of sulfuric acid, which will be described later, revealed that the fine cracks mentioned above were not cracks that would lead to deterioration of the electrode properties.
[0056] [Example 2] A coating-type BDD electrode was obtained in the same manner as in Example 1, except that the mass ratio of BDDP to tetraethoxysilane (BDDP:tetraethoxysilane) was 2:8.
[0057] [Example 3] A coating-type BDD electrode was obtained in the same manner as in Example 1, except that the mass ratio of BDDP to tetraethoxysilane (BDDP:tetraethoxysilane) was 2:8 and the firing temperature was 200°C.
[0058] [Comparative Example 1] The electrodes used were thin-film diamond (BDD) electrodes fabricated as described below using a low-resistance silicon wafer as a substrate. (Fabrication of thin-film BDD electrodes) A thin-film BDD electrode was fabricated by growing a BDD layer on the substrate surface using microwave plasma CVD. Acetone was used as the carbon source, boron oxide was used as the boron source, and the ratio of the number of boron atoms to the number of carbon atoms (boron / carbon) was set to 10,000 ppm. The CVD conditions are shown below. <CVD conditions> Microwave power: 5500W Pressure: 90 Torr Hydrogen gas flow rate: 500sccm Boron / Carbon Ratio: 10,000ppm Growth time: 4h
[0059] [Comparative Example 2] Titanium plates were used as electrodes.
[0060] As a result of CV, as shown in Fig. 2, the thin-film diamond electrode of Comparative Example 1 showed a wide potential window of about 3 V, and the rise of the oxygen generating current was observed near +2.2 V vs. Ag / AgCl. In contrast, in Comparative Example 2, the rise of the oxygen generating current was observed near +1.2 V vs. Ag / AgCl. The coated BDD electrodes of Examples 1 to 3 all showed a wide potential window of 3 V or more, and a rise in oxygen evolution current was observed at +1.8 V vs. Ag / AgCl or more, and were therefore electrodes usable for sulfuric acid electrolysis.
[0061] As shown in Fig. 3, in the constant current electrolysis of sulfuric acid (1M H2SO4), in Comparative Example 2, the electrolysis potential shifted significantly to a high potential immediately after the start of electrolysis, which was believed to be due to an increase in resistance caused by the formation of an oxide film on the titanium plate surface. In Example 3, the electrolysis potential also shifted to a high potential immediately after the start of electrolysis, which was believed to be due to an increase in resistance caused by the formation of an oxide film on the titanium substrate through the exposed portion of the titanium substrate, but the level was not problematic for use in sulfuric acid electrolysis. In Example 1, no significant increase in potential (i.e., an increase in resistance) was observed, suggesting that the titanium substrate was completely covered with the coating film (BDDP layer) and that the coating film was stable.
[0062] In the constant current electrolysis of high-concentration sulfuric acid (10M H2SO4), both Example 1 (see FIG. 4) and Comparative Example 1 remained at a stable potential, and had sufficient stability against the high-potential electrolysis of high-concentration sulfuric acid.
[0063] As shown in Fig. 5, the concentration of oxidizing active species increased with increasing current density, i.e., with increasing amount of electric charge passed through the current. This suggests that the oxidizing active species are substances generated by the electrolysis of sulfuric acid. Moreover, the generation efficiency of the oxidizing active species in Example 1 was 6.2 μmol / C at 0.3 mA, as shown in Fig. 5. For Comparative Example 1, when constant current electrolysis (5 mA) was performed so as to obtain a similar potential (near +2.8 V vs. Ag / AgCl) although the current value was different, the generation efficiency of the oxidizing active species was 5.3 μmol / C, which was found to be the same as that of Example 1.
[0064] The above results suggest that the coated diamond electrode of the present embodiment is capable of producing electrolytic sulfuric acid with the same production efficiency as the thin-film BDD electrode, and can be used as a sulfuric acid electrolysis electrode that can be made large-area. [Industrial Applicability]
[0065] The electrode of the present invention has high durability even under harsh electrolytic conditions of strong acid and high voltage, and has excellent electrolytic performance equal to or better than that of a thin-film BDD electrode, while being inexpensive and capable of being made large in area. Therefore, the electrode can be suitably used for recycling composite materials (such as carbon fiber composite materials) using an electrolytic sulfuric acid method, removing organic material patterns and / or impurities from substrates in semiconductor manufacturing, etc.
Claims
1. A method for producing a conductive diamond electrode, comprising: The conductive diamond electrode is An electrode having a substrate and a layer of conductive diamond powder on a surface of the substrate, The conductive diamond powder layer includes at least a conductive diamond powder and a matrix mainly including an inorganic material, the inorganic material primarily comprises silica; However, a conductive diamond electrode except that the conductive diamond powder layer is bonded to at least one surface of the substrate by a conductive brazing material; The method for producing the conductive diamond electrode includes the steps of: a slurry preparation step of preparing a slurry in which a powder containing a conductive diamond powder and a matrix forming material that forms a matrix of the conductive diamond powder layer are dispersed; a coating step of coating a substrate with the slurry prepared in the slurry preparation step to form a coating layer; a film-forming step of forming a film by subjecting the coating layer formed in the coating step to a heat treatment; having The matrix forming material is tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltriisopropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltriisopropoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltriisopropoxysilane, butyltrimethoxysilane, butyltriethoxysilane, butyltriisopropoxysilane, hexyltrimeth silane, hexyltriethoxysilane, hexyltriisopropoxysilane, octyltrimethoxysilane, octyltriethoxysilane, octyltriisopropoxysilane, decyltrimethoxysilane, decyltriethoxysilane, decyltriisopropoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane, octadecyltriisopropoxysilane, vinylchlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl (meth)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, p-aminophenyltrimethoxysilane, p-styryltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatopropyltriethoxysilane, 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane, A method for producing a conductive diamond electrode.
2. The method for producing a conductive diamond electrode according to claim 1, wherein the surface of the conductive diamond powder has an oxygen atom concentration of 1% or more as calculated using X-ray photoelectron spectroscopy (XPS).
3. A method for producing a conductive diamond electrode as described in claim 1 or 2, wherein the content of inorganic material in the matrix is 90 mass% or more.
4. The method for manufacturing an electrode according to any one of claims 1 to 3, wherein a mass ratio of the conductive diamond powder to the silica (conductive diamond powder:silica) is 2:8 to 8:
2.
5. The method for producing a conductive diamond electrode according to any one of claims 1 to 4, wherein the conductive diamond powder has an average particle size of 5 nm to 100 µm.
6. The method for producing a conductive diamond electrode according to any one of claims 1 to 5, wherein the conductive diamond powder layer has an average thickness of 5 nm to 500 µm.
7. A method for producing a conductive diamond electrode according to any one of claims 1 to 6, wherein the mass ratio of the conductive diamond powder to the matrix forming material (conductive diamond powder / matrix forming material) is 25 to 400 mass%.
8. A method for producing a conductive diamond electrode according to any one of claims 1 to 7, wherein the coating step is performed by a spin coating method.
9. A method for producing an electrolysis unit, comprising: producing a conductive diamond electrode using the method for producing a conductive diamond electrode according to any one of claims 1 to 8; and using the obtained conductive diamond electrode.
10. Use of an electrolysis unit, characterized in that an electrolysis unit is manufactured using the manufacturing method for an electrolysis unit described in claim 9, and the obtained electrolysis unit is used for electrolysis of sulfuric acid.
11. an electrolysis unit manufacturing step of manufacturing an electrolysis unit using the manufacturing method for an electrolysis unit according to claim 9; a solution preparation step in which sulfuric acid is electrolyzed using the electrolysis unit obtained in the electrolysis unit manufacturing step to obtain a solution containing an oxidizing active species; a removing step of removing an organic material pattern and / or impurities from a semiconductor substrate using the solution containing the oxidizing active species obtained in the solution preparing step; A method for manufacturing a semiconductor, comprising the steps of:
12. an electrolysis unit manufacturing step of manufacturing an electrolysis unit using the manufacturing method for an electrolysis unit according to claim 9; a solution preparation step in which sulfuric acid is electrolyzed using the electrolysis unit obtained in the electrolysis unit manufacturing step to obtain a solution containing an oxidizing active species; a reinforcing material recovery step of decomposing the resin of a composite material composed of a resin and a reinforcing material using the solution containing the oxidizing active species obtained in the solution preparation step, and extracting the reinforcing material; A method for treating a composite material, comprising:
13. A method for producing a composite material, comprising using a reinforcing material extracted by the method for treating a composite material according to claim 12.
Citation Information
Patent Citations
Wire saw and its manufacture
JP1999048035A
Diamond electrode for electrolysis
JP2004332108A
Diamond electrode and production method therefor
JP2005325417A
electrode
JP2006527794A
Ozone water generating apparatus
JP2008266718A